Iron loss in fortified wheat flour during Pan de sal processing - Tañag, Janine D.; Francisco, Maria Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
The total iron content of unfortified and fortified hard wheat flour was determined spectrophotometrically using the modified AACC 40-41B method. The initial iron content of unfortified flour and fortified flour were 44.595 ppm and 74.275 ppm respectively. Gradual decrease in the iron content of both types of flour was observed within the storage period of 4 weeks. On the fourth week of storage iron content of unfortified flour depreciated to a level of 20.279 ppm, while iron content of fortified flour decreased to 27.473 ppm. The flours were then processed into pan de sal with the iron content at various stages of processing determined utilizing same method of analysis. Changes in iron content was noted and it was found out that mixing and fermentation caused the iron content to increase while kneading, pan proofing, and baking resulted in substantial iron loss. Further investigation revealed that mean iron loss of 34% occurred in unfortified flour whereas 48% was the mean iron loss detected in fortified sample due to processing. Statistical analysis of data suggested that processing had no significant effect on the iron loss in unfortified wheat flour, however significant iron loss was observed from fortified wheat flour upon processing. Results showed that processing had a greater effect on the iron content of fortified flour as compared to unfortified flour.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Flour; Enriched foods